The Effect of Price and Brand Image on Oreo Buying Interest at PT Delada Cahaya Mas Agro Gunungsitoli - Irfan Zega; Maria Magdalena Bate'e; Serniati Zebua; Idarni Harefa (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the influence of price and brand image on consumer purchase intention of Oreo products at PT. Delada Cahaya Mas Agro Gunungsitoli. This research employed a quantitative method with an associative approach. The population consisted of all consumers who had purchased Oreo products, and a purposive sampling technique was applied to select 60 respondents. Data collection was conducted using a structured questionnaire, and the results were analyzed through classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The findings reveal that price has a positive and significant effect on purchase intention (t = 2.124 > 1.986, p = 0.036 < 0.05). Similarly, brand image exerts a positive and significant influence on purchase intention (t = 7.770 > 1.986, p = 0.000 < 0.05). Simultaneously, price and brand image positively and significantly affect purchase intention (F = 61.220 > 3.09, p = 0.000). The R² value of 0.476 indicates that these variables explain 47.6% of the variance in purchase intention, while the remaining 52.4% is influenced by other factors. These results highlight the strategic importance of price setting and strengthening brand image in enhancing consumer purchase interest.